Financing Social Innovation for Poverty Reduction: A Case Study of Microfinancing and Microenterprise Development in Bangladesh. (July 2014) - Mahmuda, Ismat; Baskaran, Angathevar; Pancholi, Jatin
Microfinancing is widely perceived to contribute towards social innovation for poverty reduction. We examined the Challenging the Frontiers of Poverty Reduction (CFPR) programme implemented by the Bangladesh Rural Advancement Committee (BRAC) between 2002 and 2007, as it used an innovative approach to microfinancing by transferring assets rather than cash to ultra poor participants. We examined two aspects: (i) the impact of microfinancing through asset transfer instead of cash on social innovation leading to poverty reduction; (ii) the factors that contributed to positive or negative impact on the economic conditions and poverty levels of the participant households and the trajectories of changes experienced by the success and failure cases. For this, we employed survey data from twenty-one beneficiaries and eight in-depth interviews among these households. The study found that participants who demonstrated proper planning, hard work and personal interest in the enterprise through microfinancing have witnessed improved quality of life and poverty reduction, while lack of motivation, absence of proper planning and certain social barriers resulted in failure. Our study makes two major contributions: (i) it fills a gap in the literature on microfinancing of social innovation to help ultra poor households to graduate out of poverty; (ii) it provides policy alternatives for designing appropriate microfinancing programmes for ultra poor which can produce high success rates in reducing poverty through social innovation not only in Bangladesh, but also in other developing countries.